Seafloor surficial sediment variability across the abyssal plains of the central and eastern pacific ocean - Harrison, Devin; Kolbusz, Jessica L.; Bond, Todd; Macdonald, Catriona; Niyazi, Yakufu; Jamieson, Alan J.; Stewart, Heather A. (Frontiers in Earth Science, 2025)
Abyssal plains lie at water depths of 3,000–6,000 m and account for 84.7% of the global ocean seafloor. This vast landsystem is believed to be one of the major reservoirs of biodiversity within the deep-sea. However, it is also one of the least explored parts of the ocean due to the logistical challenges of exploring at great depths over vast spatial scales. This work presents the first results of the Trans-Pacific Transit (TPT), a six-leg expedition that collected remote imagery and video footage of the seafloor sediments and substrate habitats of the central and eastern Pacific Ocean. Qualitative analysis of lander footage revealed that the surficial sediment coverage identified during the TPT survey is dominated by calcareous sediments, clays, and radiolarian sediments. The spatial distribution of these sediments is mostly consistent with previously suggested predictive distribution models. In comparison, polymetallic nodules are more pervasive across the Pacific Ocean than previously suggested. Several previously unknown nodule sites have been identified and are predominantly located in the clay-dominated seafloor of the North Pacific Ocean. Some of the newly identified nodule fields are located between 0 and 15° S in the proximity of French Polynesia. All identified nodule sites within the TPT dataset coincide with reduced rates of sedimentation and lower levels of surface Chlorophyll-a. The TPT expedition provides new insights into the seafloor sediment variability and polymetallic nodule distribution over a vast section of the Pacific Ocean, representing an unprecedented scale for modern surveys.